Pengaruh Kepemimpinan Transformasional dan Pemanfaatan PMM Terhadap Kompetensi Pedagogik Guru SMA - Supartiningsih, Supartiningsih; Abdullah, Ghufron; Nurkolis, Nurkolis (PGRI Kota Semarang, 2024)
The background to this research problem is related to the pedagogical competence of teachers at SMA Negeri Sub Rayon Barat Batang Regency who are not good at understanding students in depth, designing learning, implementing learning, designing and carrying out learning evaluations, developing students' potential. The transformational leadership of school principals and the use of the independent teaching platform (PMM) have not been able to optimally improve teachers' pedagogic competence. Based on the explanation above, research was carried out on the influence of the principal's transformational leadership and the use of PMM on the pedagogic competence of teachers at the West Batang Sub Rayon State High School, Batang Regency.This research aims to determine: (1) the influence of the principal's transformational leadership on teachers' pedagogical competence, (2) the influence of the use of PMM on teachers' pedagogical competence, (3) the simultaneous influence of the principal's transformational leadership and the use of PMM on teachers' pedagogic competence.Population of 196 people, sample of 130 people. The instrument test used is the validity and reliability test. Test the classical assumptions/prerequisites using the normality test, homogeneity test, linearity test, and heteroscedasticity test. Data analysis uses regression test, F test and t test.Based on the research results, it can be concluded as follows: (1) the principal's transformational leadership has a positive and significant effect on the pedagogic competence of teachers at Batang Sub Rayon State High School as proven by a Sig value of 0.000 < 0.05 and tcount 10.828 > ttable 1.979. The magnitude of the influence is 66.7%; (2) the use of the independent teaching platform (PMM) has a positive and significant effect on the pedagogic competence of teachers at West Batang Sub Rayon State High School as proven by the Sig value of 0.005 < 0.05 and tcount 7.738 > ttable 1.979. The magnitude of the influence is 51.9%; (3) the principal's transformational leadership and the use of PMM simultaneously have a positive and significant effect on teacher pedagogic competence as proven by the Fcount value of 47.033 > Ftable 3.070 with a significance level of 0.000 < 0.05. The magnitude of the influence is 62.6%.The suggestions put forward by researchers are: (1) for school principals, be able to continue to improve their transformational leadership, especially the inspirational motivation dimension and encourage teachers to utilize PMM; (2) for teachers, they are able to increase their competence, especially developing the potential of students, one of which is by optimizing the use of PMM.